Avaliação de usabilidade em um sistema agrícola web - Oliveira, Monique Emidio de (2022)
With the new technologies present today, mainly computer systems, it is necessary to apply methods to evaluate these usability systems, verifying if usability systems are adequate. Although the use of information technology still has some reluctance in certain domains, such as agriculture, it is necessary, since many, such as monitoring and brings benefits of useful information, which enables correct decision-making, increasing productivity in a sustainable way. . However, the systems still bring difficulties to their users, they cannot find what they need due to the excess of information in the interfaces, making it impossible to interpret the data. Therefore, the study of usability in web systems is relevant, allowing the tasks of visualization and insertion of information to be performed clearly and easily. Embrapa So problems and plants of attempts to develop a decision-making platform, to provide information on soybean systems, diseases and plantation that allows the identification of soybean decision plants. This work aimed to develop and evaluate the usability of a web system to identify pests, diseases and weeds, intended for soybean producers and system administrators, who are professionals from Embrapa Soja – Londrina). The was implemented using Wordpress, and the usability was performed with a user application (SUS – System Usability Scale and UEQ User Experience uestionnaire) system and user profile evaluation, with a participatory platform of 15 participants among the participants of the system and farmers. In both, the usability level of the system was considered excellent, according to the details.